2003
DOI: 10.1002/syn.10240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an adenosine A2A receptor blockade in the nucleus accumbens on locomotion, feeding, and prepulse inhibition in rats

Abstract: The nucleus accumbens (NAc) subserves behaviors governed by natural rewards, i.e., feeding or exploration, and has been implicated in control of prepulse inhibition (PPI), a measure of sensorimotor gating. The present study sought to determine whether a tonic stimulation of adenosine A(2A) receptors in the rat NAc is involved in control of spontaneous locomotor activity, feeding behavior, and PPI. To this end, bilateral microinfusions of a prodrug (MSX-3) (3 microg and 5 microg in 1 microl per side) of the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 47 publications
8
36
0
Order By: Relevance
“…Effect size analyses indicated that MSX-3 produced moderate-to-large effects when injected into nucleus accumbens core. These positive effects obtained with MSX-3 injections into the core clearly demonstrate that nucleus accumbens is an effective site for the stimulation of locomotion by MSX-3 in haloperidol-treated rats, an observation that is consistent with previous studies showing that adenosine A 2A receptors in nucleus accumbens are involved in the regulation of locomotion [6,7,31,59]. However, the robust and consistent effects observed after injections of MSX-3 into the nucleus accumbens core were not mimicked by injections into the dorsomedial shell.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Effect size analyses indicated that MSX-3 produced moderate-to-large effects when injected into nucleus accumbens core. These positive effects obtained with MSX-3 injections into the core clearly demonstrate that nucleus accumbens is an effective site for the stimulation of locomotion by MSX-3 in haloperidol-treated rats, an observation that is consistent with previous studies showing that adenosine A 2A receptors in nucleus accumbens are involved in the regulation of locomotion [6,7,31,59]. However, the robust and consistent effects observed after injections of MSX-3 into the nucleus accumbens core were not mimicked by injections into the dorsomedial shell.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, doses of MSX-3 that reversed haloperidol-induced lever pressing had no effects when injected without the DA antagonist [23]. Although recent work has indicated that intra-accumbens injections of MSX-3 can increase locomotion [59], that paper used behavioral methods that were substantially different from those used in the present study (i.e., open-field activity in habituated animals). Moreover, previous studies showing that systemic injections of MSX-3 increased locomotion used younger rats than the present study [2,41,72].…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations